Potentially Beneficial Effects on Healthy Aging by Supplementation of the EPA-Rich Microalgae Phaeodactylum tricornutum or Its Supernatant—A Randomized Controlled Pilot Trial in Elderly Individuals - Lena Stiefvatter; Konstantin Frick; Katja Lehnert; Walter Vetter; Alexander Montoya-Arroyo; Jan Frank; Ulrike Schmid-Staiger; Stephan C. Bischoff (Marine Drugs, 2022)
Dietary supplements that promote healthy aging are mostly warranted in an aging society. Because of age-related risks, anti-inflammatory and anti-oxidative agents such as microalgae are potential candidates for intervention. In a randomized controlled trial, we tested Phaeodactylum tricornutum (PT), a microalgae rich in eicosapentaenoic acid (EPA), carotenoids, vitamins, and β-glucans, cultured in bioreactors. In this pilot trial, 19 healthy elderly received supplements for two weeks based on either the whole PT (A), the β-1,3-glucan-rich PT supernatant (SupB), the combination thereof (A+SupB), or a Comparator product (Comp). The primary outcome variable plasma interleukin-6 was reduced after treatment with A+SupB compared to the Comp group (p = 0.04). The mobility parameters 5 s sit-to-stand test (p = 0.04 in the A group) and by trend gait speed (p = 0.08 in the A+SupB diet) were improved compared to Comp. No treatment effects were observed for fatty acids, compared to Comp but omega-6 to -3 fatty acid ratio (p = 0.006) and arachidonic acid/EPA ratio (p = 0.006) were reduced within group A+SupB. Further, the SupB study product reduced faecal zonulin (p = 0.03) compared to the Comp. The data revealed an anti-inflammatory and potentially anti-oxidative effect of particular PT preparations, suggesting that they might be suitable for effects in healthy elderly.